2014
DOI: 10.1002/2014gb004850
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight‐induced carbon dioxide emissions from inland waters

Abstract: The emissions of carbon dioxide (CO 2 ) from inland waters are substantial on a global scale. Yet the fundamental question remains open which proportion of these CO 2 emissions is induced by sunlight via photochemical mineralization of dissolved organic carbon (DOC), rather than by microbial respiration during DOC decomposition. Also, it is unknown on larger spatial and temporal scales how photochemical mineralization compares to other C fluxes in the inland water C cycle. We combined field and laboratory data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
192
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(221 citation statements)
references
References 65 publications
17
192
4
Order By: Relevance
“…Furthermore, we demonstrated that when DOC has a higher proportion of chromophoric structures (as indicated by a high SUVA254) it is more susceptible to being completely mineralised to CO2. This supports findings from previous studies (Dehaan 1993;Koehler et al 2014) and highlights how DOC leaching from peatlands is particularly susceptible to photo-degradation. The 14-17% reduction in DOC concentration of the unfiltered peatland stream solution after exposure to a dose of solar radiation equivalent to one sunny mid-summer day demonstrates that a significant proportion of DOC may be photo-degraded during transport down the river system, despite the relatively short residence time.…”
Section: Susceptibility Of Contrasting Waters To Photo-degradationsupporting
confidence: 91%
“…Furthermore, we demonstrated that when DOC has a higher proportion of chromophoric structures (as indicated by a high SUVA254) it is more susceptible to being completely mineralised to CO2. This supports findings from previous studies (Dehaan 1993;Koehler et al 2014) and highlights how DOC leaching from peatlands is particularly susceptible to photo-degradation. The 14-17% reduction in DOC concentration of the unfiltered peatland stream solution after exposure to a dose of solar radiation equivalent to one sunny mid-summer day demonstrates that a significant proportion of DOC may be photo-degraded during transport down the river system, despite the relatively short residence time.…”
Section: Susceptibility Of Contrasting Waters To Photo-degradationsupporting
confidence: 91%
“…Thus, the relative role that UV light processing played for the DOC quality transformations was much larger in clear lakes than in highly colored lakes. In absolute terms, however, some studies suggest that the absolute light-induced color loss is similar for brown and clear lakes given equal incoming surface irradiation, even if this loss in color is distributed in different ways over the water column (Granéli et al, 1996;Koehler et al, 2014). In our study the mean absolute a 420 loss in the four clearest epilimnetic sites was 1.0 m −1 year −1 (Fig.…”
Section: Organic Carbon Transformation Processesmentioning
confidence: 43%
“…A fundamen-tally important water-column process that generates carbon dioxide (CO 2 ) is the microbial degradation of terrestrially derived DOC (Lapierre et al, 2013;Fasching et al, 2014). Significant amounts of DOC can also be mineralized by ultraviolet (UV) sunlight in lakes (Koehler et al, 2014) and running waters (Cory et al, 2014). However, while much research attention has been drawn to CO 2 production from these different processes, surprisingly little is known about the relative role played by biological and photochemical processes for DOC quality transformations and, in particular, for the removal of color.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that sunlight can play an important role in dissolved organic matter (DOM) degradation in thermokarst-impacted lakes and ponds (Alaska, Cory et al, 2013Cory et al, , 2014Canadian High Arctic, Laurion and Mladenov, 2013; sub-Arctic Sweden, Koehler et al, 2014). To understand why sunlight can be an important control on DOM degradation in these systems, we review controls on DOM photodegradation and the specific characteristics of thermokarst lakes that can maximize opportunities for photodegradation.…”
Section: Photodegradation Of Organic Carbonmentioning
confidence: 99%
“…Clouds generally decrease surface UV, but the effect of clouds can be offset by ozone levels, making it difficult to predict surface UV based only on latitude and date across the Arctic (Vavrus et al, 2010;Bernhard et al, 2013). Although less UV generally reaches surface waters in the Arctic compared to lower latitudes due to lower solar zenith angles, thermokarst lakes and ponds can often have high concentrations of light-absorbing DOM that is susceptible to photo-degradation, thus potentially counter-balancing the lower UV (Alaska, Cory et al, 2014; sub-Arctic Sweden, Koehler et al, 2014).…”
Section: Photodegradation Of Organic Carbonmentioning
confidence: 99%